(untitled) - Birsch, Douglas (Boston, 2001)
This is a brief, accessible, affordable supplement for any applied ethics course. The text covers eight ethical theories, with each chapter focusing on a key ethical insight that helps establish moral guidelines to solve ethical problems
Keywords: Ethics,Đạo đức học